Voices from the Margin: A Subaltern Reading of Mahasweta Devi’s Rudali - Sharma, Shyam Prasad (Pragnya Sarathi, 2026)
This paper analyses the formation of subaltern subjectivity through the intersecting structure of caste, class, and gender in Mahasweta Devi's Rudali, a novella, as the primary site of interpretation. Although the text has been widely examined through feminist and Marxist framework, comparatively less attention has been paid to the ways subaltern agency operates within these interlocking systems of domination. By addressing this lacuna, this study foregrounds the dynamic processes through which subaltern identities are constituted and negotiated under the conditions of structural subjugation. The analysis is grounded in the theoretical framework of Subaltern Studies, draws the ideas of Gayatri Chakravorty Spivak from her work "Can Subaltern Speak? Ranjit Guha's ideas as articulation of subaltern agency and consciousness, autonomous agents whose consciousness and actions cannot be reduced to elite politics, since their insurgencies arise from their own experiences, values, and modes of organization rather than from elite leadership. Antonio Gramsci's concept of cultural hegemony; rule with consent, the domination is sustained not only through coercion but also through the internalization of ruling values proves particularly illuminating. In the text, Sanichari and other marginalized women come to accept suffering, poverty, and social exclusion as inevitable conditions of existence; hegemony thus, operates at the level of consciousness. The institution of professional mourning emerges as both a symbolic and material practice that reinforces castes and class hierarchies, enabling the exploitation of subaltern women while simultaneously legitimizing dominant authority. Employing a qualitative analysis this study argues that subaltern identity is not merely imposed but continually negotiated. Sanichari’s transformation of socially imposed suffering into a means of economic survival gestures toward a subtle yet significant form of resistance. By foregrounding the subaltern body and its lived realities, Devi constructs a counter hegemonic narrative space that renders visible limited yet significant forms of subaltern agency, not merely as a critique of systematic oppression, but also as an exploration of alternative albeit constrained modes of resistance from marginalized subjects.